AN ANALYSIS OF THEMES IN "THE MAGIC"AND ITS INDONESIAN TRANSLATION - Riani, Dewi (2014)
The present study entitled An Analysis of Themes in "The Magic"and Its Indonesian Translation (A Systemic Functional Grammar Approach) aims to find out the types of Theme and Thematic Progression in the original version and the translated version of The Magic and Themes realization in the Indonesian translated version. This study employed a descriptive qualitative method especially textual analysis.The present study adopted Halliday's (1994) theory of Systemic Functional Grammar as a tool to analyze the Themes used in the texts and also Eggins' (2004) theory of thematic progression.The study found that in the source text and in the target text, there are three types of Theme found out. Those are Topical Theme, Textual Theme and Interpersonal Theme. Moreover, the types of Thematic Progression in source text and target text show the same pattern. The finding also shows that there are four pattern of Theme realization in translation text. The first pattern, the Themes are translated like the original. The second pattern, part of Theme is ellipted. The third pattern, there are some words from Rheme translated as Theme. The last is the Themes are shifted in the process of translation. The realization of Theme also does not affect the Thematic Progression. Studi ini, yang berjudul An Analysis of Themes in "The Magic"and Its Indonesian Translation (A Systemic Functional Grammar Approach) bertujuan untuk mengidentifikasi jenis Theme dan Thematic Progression pada teks asli dan teks terjemahan versi Indonesia serta realisasi Theme dalam versi terjemahan Indonesia. Studi ini menggunakan metode deskriptif kualitatif dengan analisis teks. Studi ini mengadaptasi teori Halliday (1994) tentang Systemic Functional Grammar sebagai sebuah alat untuk menganalisi Theme yang digunakan dalam teks dan juga teori Eggins (2004) tentang Thematic progression. Studi ini menemukan bahwa dalam teks target dan teks sumber ditemukan tiga jenis Theme, yaitu Topical Theme, Textual Theme and Interpersonal Theme. Selain itu juga, jenis Thematic Progression pada teks sumber sama dengan yang berada pada teks target. Studi ini juga menemukan empat pola dalam realisasi Theme pada teks target. Pola yang pertama, Theme diterjemahkan seperti aslinya. Pola kedua, bagian dari Theme dihilangkan. Pola terakhir adalah Theme dirubah pada saat proses penerjemahan. Realisasi Theme tidak mempengaruhi Thematic Progression.